THE STUDY OF MACHINABILITY AND STRESS CORROSION CRACKING OF AISI 316L STAINLESS STEEL USING END-MILLING - ,, MUHAMMAD YASIR (2015)
End milling is a potential machining technique for difficult to cut materials such as stainless steels. The application of AISI 316L SS in biomedical field made its worth than other materials as it is economical and reliable but less corrosion resistant as compared to titanium alloys. Especially when used as an implant, to support the damaged bone, often failed before the healing of bone due to poor surface quality and re-surgery is required in order to remove that failed implant. In the literature, the machinability improvement of AISI 316L SS using end milling is not fully reported so far. Therefore, the aim of this research work is to investigate the effect of cutting parameters such as cutting speed (Vc) and feed rate (f) on the surface roughness and surface integrity of AISI 316L SS. There is a need to investigate the effect of surface roughness and surface integrity on the SCC under body fluids and HC1 solution.